Letter from the editor (2017)
It's time to present our second volume of 2017. The result of a great effort to put into your hands some works of the best quality. With this selection of articles, an invitation to the Colombian Geology Congress.As every two years, in a city strategically picked up to show the best of the Colombian and Latinamerican Geology, the Sociedad Colombiana de Geologia entity (Colombian Geology Society) presents the XVI Congress of Geology and the third Explorers Symposium. The venue is Santa Marta, a touristic city in the Caribbean. Register for technical courses and field visits are still open. The event is scheduled August 28 until September 1, 2017. Recent months, it has been confirmed in Colombia a gas reservoir with at least 520 meters of netgross at the Kronos well, which suggests a substantial increase in the gas reserves of the country. Sure, a subject to be analyzed during the Congress. The discovery, which left the first results in 2015, is proved in a depth of 4,795 meters, including a 1,835-meter water table. The state-managed company Ecopetrol holds a 50% share in this block, according to news releases by them, as the 50% remaining is of Anadarko, an operator company. These figures are on the same way that the energy reserves around the world, where new techniques and exploration have reached peaks to cover the current demand for oil and related products for decades. This growth of reserves in the world goes hand in hand with the investment. Ecopetrol, for example, announced the increase of its exploration budget this year to US$ 650 million with the final purpose of intensifying the search for new hydrocarbon reserves.But mining in the Earth would be not the unique perspective to analyze. Goldman Sachs wrote a recent note explaining that “space mining could be more realistic than perceived,” according to an interesting article published by The Washington Post on 28 April 2017. The report analyzes the possibilities and bets the mining out of the Earth is a decade away. For the next year, the NASA plans to vacuum materials from a 2,000-foot-wide asteroid called Bennu; sure it would be the cornerstone. Thanks for your attention to this number of the Earth Sciences Research Journal and the little reflections proposed in this letter. With the best regards,Carlos Alberto Vargas JimenezEditor in chief